Detrital apatite fission track evidence for provenance change in the Subei Basin and implications for the tectonic uplift of the Danghe Nan Shan (NW China) since the mid-Miocene. (1st November 2015) - Lin, Xu; Zheng, Dewen; Sun, Jimin; Windley, Brian F.; Tian, Zhonghua; Gong, Zhijun; Jia, Yingying
Highlights: We present first apatite fission track dating from the Tiejianggou Formation from the Subei Basin. Thermochronological results have revealed provenance change during the middle Miocene times. The provenance change is mainly ascribed to the uplift of the west end of Danghe Nan Shan at middle Miocene. Abstract: The Subei Basin is located at the intersection of the northeastern end of the Altyn Tagh Fault (ATF) and the western end of the Danghe Nan Shan in the northeastern Tibetan Plateau. The Basin contains (up to) 4000 m-thick Cenozoic terrestrial clastic sediments, which contain information on the uplift of the Danghe Nan Shan. In order to estimate the detrital apatite thermochronology with fission track dating, we collected eight sandstone samples from the Tiejianggou section of the Subei Basin, which has an established depositional age range from 22.8 to 9 Ma. We found that a distinct change in slope of the peak age and lag time of the detrital apatite fission track occurred at ∼14 Ma, which we interpret as a provenance change caused by the uplift of the western end of the Danghe Nan Shan. Combined with previous studies in adjacent areas, this work implies that the initiation of successive episodes of surface uplift in the northeastern margin of the Tibetan Plateau took place in the mid-Miocene.